IMF Staff Papers, Volume 55, No. 1. (IMF Staff Papers; IMF Staff Papers ;, 2008)
In this issue, a team of economists look at approaches to modeling the use of IMF resources in order to gauge whether the recent decline in credit outstanding is a temporary or permanent phenomenon. Era Dabla-Norris and Gabriela Inchauste examine what drives the growth of firms, with a focus on informality and regulations. Evan Tanner and Issouf Samake use a vector autoregression approach to examine the probabilistic sustainability of public debt in Brazil. Mexico, and Turkey. And Rachel Glennerster and Yongseok Shin ask whether transparency pays?that is, does the frequency and accuracy of macroeconomic information released to the public lead to lower borrowing costs in sovereign debt markets?